"La otra orilla" and "Sonambulario": parallels in the fantastic aspect of Julio Cortázar and Julio Ramón Ribeyro - Quichiz Campos, Gustavo Alberto (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The study of the fantastic in Julio Ramón Ribeyro (1927-1994) is still a work in progress, in the same way that Sonambulario is, his book project that aimed to gather the fantastic short stories of the first stage of his work, but that he finally dropped. A famous writer in Peru, and with cult following outside there, Ribeyro lived most of his life in Paris. He was a friend of Julio Cortázar (1914-1984), with whom he shared his way of understanding the fantastic. This paper contrasts the first short stories of both writers and the importance they reveal in the definition of twentieth-century Hispanic America fantasy literature.